The Integration of the Law of Attraction Concept in Islamic Inheritance Dispute Resolution: An Islamic Legal Perspective and Its Implications for Social Justice in Inheritance Distribution - Azizon; Nasution, Syamruddin; Maghfirah (Universitas Islam Negeri Raden Intan Lampung, 2026)
Islamic inheritance law, derived from the Qur'an and Sunnah, ensures a just distribution of wealth among heirs. However, the practical application of this law can be complicated by cultural norms and emotional dynamics within families. This study explores the integration of the Law of Attraction (LoA) concept in resolving inheritance disputes within the framework of Islamic law, particularly through the analysis of Supreme Court Decision No. 1239 K/Ag/2023 in Indonesia. The decision recognized the role of positive intentions and collective agreements among heirs, influenced by LoA principles, in achieving an equitable distribution of inheritance. By examining the interplay between LoA and Islamic inheritance law, this research highlights the potential for non-conventional approaches to contribute to more harmonious and just outcomes in legal disputes. The study finds that while LoA is not explicitly part of classical Islamic jurisprudence, its application in this context aligns with the principles of justice, fairness, and non-harm in Islamic law. This research contributes to the discourse on Islamic legal reforms and suggests that integrating psychological and emotional dimensions into legal processes can enhance social justice and inclusivity, particularly in inheritance matters. The implications for Islamic legal education and the potential alignment with the Sustainable Development Goals (SDG 16) are also discussed, offering a new perspective on legal innovation and dispute resolution.